Peran Sistem Pengendalian Internal dalam Mitigasi Risiko Fraud : Studi Kasus Proyek Waingapu - Rachmawati, Aqila; Syaiful Akbar, Fajar (Forum Kerjasama Pendidikan Tinggi, 2025)
Fraud in construction projects is a serious risk that can undermine the efficiency and accountability of project implementation. Internal control systems play a crucial role in preventing fraud, particularly in procurement and budget utilization processes. This study aims to evaluate the internal control system implemented by PT. Bangun Mitra Persada in the execution of the Waingapu Project and to assess its effectiveness in preventing fraudulent practices. This research adopts a descriptive qualitative approach, with data collected through semi-structured interviews with one internal company informant. The results show that the internal control system is implemented strictly through direct supervision by the company owner over all project expenditures, regardless of their scale. Each transaction must receive direct approval from management and must refer to the pre-established Budget Plan (RAB). In addition, employees’ understanding of market prices and their close relationships with vendors contribute to maintaining cost efficiency and reducing fraud risks. These findings indicate that direct leadership involvement, compliance with budget planning documents, and strict documentation control are key factors in effectively preventing fraud within project operations.